Essentials of Understanding Abnormal Behavior, 3rd Edition - David Sue (Cengage Learning, 2016)
This brief text offers a balanced, clear introduction to abnormal psychology and features the same sociocultural focus, multicultural emphasis, topical coverage, and engaging style of its parent text in a condensed, reader-friendly format. Fully updated to reflect the DSM-5, this edition continues to feature the Multipath Model of Mental Disorders, which visually and conceptually examines possible causes of the variety of mental disorders discussed in the text. Throughout the book, a focus on resilience highlights prevention and recovery from the symptoms of mental illness. The authors present material in a lively and engaging manner, incorporating a wealth of visuals and connecting topics to real-world case studies, current events, and issues of particular importance and relevance to today's college students.